1993
DOI: 10.1044/jshr.3605.906
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Stuttering and Disordered Phonology in Young Children

Abstract: The purpose of the present study was to assess differences in stuttering, phonological, and diadochokinetic behaviors in young children who exhibit both stuttering and disordered phonology and children who exhibit only one of the disorders. Subjects were 21 male children (aged 4 to 6 years), representing three groups of seven children each: (a) stuttering and normal phonological abilities ( S+NP ), (b) stuttering and disordered phonology ( S+DP ), and (c) normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 31 publications
5
50
0
2
Order By: Relevance
“…Stuttering children in the experimental group this number increases to 60%. These results are similar to another study 28,29 . The statistical analysis in Table 2 showed that the observed difference in the incidence of phonological processes between groups were not statistically significant.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Stuttering children in the experimental group this number increases to 60%. These results are similar to another study 28,29 . The statistical analysis in Table 2 showed that the observed difference in the incidence of phonological processes between groups were not statistically significant.…”
Section: Resultssupporting
confidence: 82%
“…There is a qualitative difference found between stuttering and non-stuttering children 12 related to the type of linguistic unit where disfluencies occurred: children with stuttering and disfluency on phonemes and syllables were more frequent, not stuttering children, treated the whole word, sintagma and/ or sentence. Another study investigated issues between phonology and fluency and observed that stuttering children with phonological disorder did more prolongations in speech and repetition of words when compared with children who stutter, but that had no phonological disorder 28 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Slowness during oral DDK tasks in dyslexic children was a result not only of phonologic access and motor planning but also of slower velocity in the production of the articulatory gesture [15] . There is still the need to understand the relationship between DDK and phonological ability, DDK and speech articulatory rates, besides DDK and speech fluency [11] .…”
Section: Discussionmentioning
confidence: 99%
“…The DDK test has been used in the assessment of children with several speech alterations [11] , as well as in adults with neurological diseases [12] and patients who were submitted to laryngeal vertical hemilaryngectomy [13] . DDK associated with other…”
mentioning
confidence: 99%